2007
DOI: 10.4315/0362-028x-70.4.958
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Population, Physicochemical Quality, and Allergenicity of Molluscs and Shrimp Treated with Cobalt-60 Gamma Radiation

Abstract: Frozen molluscs (squid, octopuses, and cuttlefish) and crustaceans (shrimp) were irradiated using a cobalt-60 gamma source, at different doses, in order to investigate the effects of gamma radiation on their microbial population, organoleptic characteristics, lipid profile, and tropomyosin content. Irradiation of shrimp and squid with either 2.5 or 4.7 kGy reduced mesophilic bacteria contamination to low or nondetectable levels, respectively, whereas irradiation of octopus and cuttlefish with the same doses re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Sinanoglu et al [43] completely inactivated the allergen shrimp tropomyosin by irradiating them at a dose of 4.5 kGy confirming the results of Zhenxing et al [44] but found that at doses lower than 5 kGy allergenicity increases. Leszczynska et al [45] used doses up to 12.8 kGy in wheat flour gliadin irradiation and noted small increase in ɷ-gliadin as the dose of radiation increases.…”
Section: New Insights On Gamma Raysmentioning
confidence: 58%
“…Sinanoglu et al [43] completely inactivated the allergen shrimp tropomyosin by irradiating them at a dose of 4.5 kGy confirming the results of Zhenxing et al [44] but found that at doses lower than 5 kGy allergenicity increases. Leszczynska et al [45] used doses up to 12.8 kGy in wheat flour gliadin irradiation and noted small increase in ɷ-gliadin as the dose of radiation increases.…”
Section: New Insights On Gamma Raysmentioning
confidence: 58%
“…Ito et al [69] reported that the dose of gamma irradiation necessary to reduce both S. typhimurium and L. monocytogenes in frozen shrimps at a level of below 10 −4 per gram was about 3.5 kGy. Sinanoglou et al [70] irradiated using a cobalt-60 gamma source frozen molluscs (squid, octopuses, and cuttlefish) and crustaceans (shrimp) with different doses. The authors noted the substantial decrease of mesophiles number in shrimp irradiated with the dose of 2.5 kGy, whereas after the dose of 4.7 kGy the presence of those bacteria in squid was not detected.…”
Section: Reducing Salmonella Spp In Fish and Shellfishmentioning
confidence: 99%
“…In their trail, the authors found that the rejection of octopus kept in crushed ice occurs at day 8. Several attempts were carried out to increase the shelf life by an appropriate treatment (high pressure, heat combined to high pressure, gamma radiation) and to improve the textural properties inducing the softening of meat (Hurtado et al, 2001a(Hurtado et al, , 2001b(Hurtado et al, , 2001cSinanoglou et al, 2007). Recently, Mendes et al (2011) tested the active packaging based on soluble CO2 stabilisation (SGS) methodology to obtain readyto-eat products.…”
Section: Qualitymentioning
confidence: 99%